AB0308 Delay in referral and diagnosis of rheumatoid arthritis in a community medical center in japan. (23rd January 2014) - Kimura, M.; Yoshida, K.; Oshikawa, H.; Kobayashi, T.; Nakano, H.; Utsunomiya, M.; Kishimoto, M.; Matsui, K.
Abstract : Background: Much emphasis has been placed on early diagnosis and treatment of rheumatoid arthritis (RA) 1 . In order to achieve the better outcome, the timing of referral and diagnosis of early arthritis should be optimized 2 . Objectives: To examine the time to referral of patients with early arthritis, and diagnosis delay of RA in a rural community medical center in Japan. Methods: A total of 296 who visited Kameda Medical Center from January 2009 to December 2010 with at least one swelling joint without any previous treatment were included. In the patients diagnosed as RA, the time intervals from the onset of symptom to primary care physician (PCP) (patient delay), from PCP referral to a rheumatologist (PCP delay), from the onset of symptoms to rheumatology visit (total delay) were determined. Results: Ninety-four patients were diagnosed as having RA. The median patient, PCP, total delays [interquartile range [IQR]] were 8.8 weeks [3.4-30.1], 5 weeks [1.9-20.1], 26.9 weeks [10.9-69.4] respectively. The patient delay was significantly longer than PCP delay (p=0.046). Twenty-seven (29%) RA patients were assessed within 12 weeks from onset. At baseline, these patients had less bone erosion on radiograph, as compared with those assessed after≥12 weeks (7% vs 30%, p=0.03). Conclusions: In a rural community medical center in Japan, the patient delay is longer than the PCP delay, which is comparable to earlier reports from Europe 3 . This study indicates the key delay in early arthritis diagnosis in Japan. References: P, et al. Ann Rheum Dis 2002;61:290-7. Van der Linden MP, et al. Arthritis Rheum 2010;62:3537-46. K.Raza, et al. Ann Rheum Dis 2011;70:1822-1825 Disclosure of Interest: None Declared